Global decline of apex scavengers threatens human health - Chinmay Sonawane; Maya Xu; Natalie Ward; Ariella Chichilnisky du Lac; Bohdan Kamets; Rodolfo Dirzo (Proceedings of the National Academy of Sciences, 2025)
Vertebrate scavengers play a critical role in ecosystem functioning worldwide. Through the cascading effects of their ecological role, scavengers can also alleviate the burden of zoonotic diseases on people. This importance to human health fuels a growing need to understand how vertebrate scavengers and their ecosystem services are faring globally in the Anthropocene. We reviewed the conservation status of 1,376 vertebrate scavenging species and examined the implications for human health. We uncovered that 36% of these species are threatened or decreasing in population abundance and that apex (large-bodied or obligate) scavengers are disproportionately imperiled. In contrast, mesoscavengers (small-bodied or facultative) are thriving from anthropogenic food subsidies and ecological release. We posit that this global shift in scavenger community structure increases carrion persistence enabling zoonotic pathogens to propagate. Our analysis also indicates that the release of mesoscavengers is associated with reservoir host proliferation, potentially further exacerbating human disease burdens. Urgently tackling the key threats to scavengers—intensive livestock production, land use change, wildlife trade, and the interactions among them—is critical to securing the long-term public health benefits of the world’s diverse scavenger communities.